2018
DOI: 10.1016/j.cct.2018.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Workplace health and safety intervention for child care staff: Rationale, design, and baseline results from the CARE cluster randomized control trial

Abstract: Background Low-wage workers suffer disproportionately high rates of chronic disease and are important targets for workplace health and safety interventions. Child care centers offer an ideal opportunity to reach some of the lowest paid workers, but these settings have been ignored in workplace intervention studies. Methods Caring and Reaching for Health (CARE) is a cluster-randomized controlled trial evaluating efficacy of a multi-level, workplace-based intervention set in child care centers that promotes ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(50 citation statements)
references
References 71 publications
0
43
0
5
Order By: Relevance
“…The proportion of providers meeting recommendations for fruit and vegetable consumption (3.5 cups or 5 servings per day) varied from 22.5% of Head Start staff [17] to 50% of family child care (FCC) providers [32]. Mean fruit and vegetable consumption exceeded recommendations in one study of Head Start teachers [16] but were below recommendations in one study of child care center (CCC) directors and staff [9].…”
Section: Diet Qualitymentioning
confidence: 97%
See 4 more Smart Citations
“…The proportion of providers meeting recommendations for fruit and vegetable consumption (3.5 cups or 5 servings per day) varied from 22.5% of Head Start staff [17] to 50% of family child care (FCC) providers [32]. Mean fruit and vegetable consumption exceeded recommendations in one study of Head Start teachers [16] but were below recommendations in one study of child care center (CCC) directors and staff [9].…”
Section: Diet Qualitymentioning
confidence: 97%
“…Five studies explored the proportion of providers meeting national physical activity requirements (e.g., 150 min per week of moderate to vigorous physical activity); the results included 27% of CCC employees [23], 29.4% of CCC directors and staff [9], and 55% of Head Start teachers [22] met these recommendations. Approximately 40-50% of FCC providers in two studies reported meeting guidelines [24,32].…”
Section: Physical Activitymentioning
confidence: 99%
See 3 more Smart Citations